Restrictions on Freedom of Investment in Shipping Industry According to Algerian Law - Bourtal, Amina (Journal of Legal Studies and Researches, 2023)
Algeria State encourages investment by granting concession for the exercise of transport activity, Given the importance of this in attracting foreign investors to exploit shipping services, However legislature has stipulate legal requirements and procedures set out in Algerian maritime law executive decree N°08-57, and law N°22-18, conclude that the Algerian state continues to intervene in this sector.